Quadrille - Borchard, Adolphe 1882-1967 (<<The>> Criterion collection, 2010)
"A sparkling four-way affair overflowing with dialogue that showcases writer-director Sacha Guitry’s wit, Quadrille stars Guitry as a magazine editor whose longtime girlfriend—to whom he plans to finally propose—is uncontrollably drawn to a handsome American movie star. Meanwhile, a discerning reporter (Jacqueline Delubac) watches from the sidelines with amusement and provides the final corner to this romantic rectangle." [criterion.com]
Original: Frankreich 1938
Bildformat 1.33:1
Keywords: Film; DVD-Video